2018
DOI: 10.1007/s00431-018-3101-6
|View full text |Cite
|
Sign up to set email alerts
|

Sport-based physical activity recommendations and modifications in C-reactive protein and arterial thickness

Abstract: Inflammation decreased in adolescents engaged in organized sports, independently of trunk fatness and biological maturation. Moreover, inflammation was related to arterial thickening only in adolescents not engaged in sports. What is Known: • Intima media thickness is a relevant marker of cardiovascular disease in pediatric groups, being affected by obesity and inflammation. • The importance of monitoring inflammatory markers from childhood is enhanced by the fact that alterations in these inflammatory markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…However, another finding related to trunk fatness in this study was the fact that sports participation and inflammation status were related with each other independently of adiposity, denoting that the association between sports participation and CRP levels has a direct pathway. Similarly, longitudinal data have identified that adolescents engaged in ≥300 min/wk of sports for at least 12 months showed a greater decrease in CRP levels than their counterparts not engaged in sports, independently of adiposity. In fact, exercise protocols seem to be able to decrease inflammatory markers even in obese adolescents, denoting that the anti‐inflammatory environment attributed to physical exercise is adiposity‐independent.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, another finding related to trunk fatness in this study was the fact that sports participation and inflammation status were related with each other independently of adiposity, denoting that the association between sports participation and CRP levels has a direct pathway. Similarly, longitudinal data have identified that adolescents engaged in ≥300 min/wk of sports for at least 12 months showed a greater decrease in CRP levels than their counterparts not engaged in sports, independently of adiposity. In fact, exercise protocols seem to be able to decrease inflammatory markers even in obese adolescents, denoting that the anti‐inflammatory environment attributed to physical exercise is adiposity‐independent.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, previous time of engagement in sports was associated with decreased levels of CRP, while trunk fatness was not a mediator of this model. Given the fact that sports participation is an enjoyable way for adolescents to achieve the recommended MVPA for health, it is important to highlight that engagement in sports may decrease pro‐inflammatory cytokines, even without significant adiposity changes …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations